Rapid Recovery of Fat Mass in Small for Gestational Age Preterm Infants after Term - Roggero, Paola (Public Library of Science, 2011)
BACKGROUND: Preterm small for gestational age (SGA) infants may be at risk for increased adiposity, especially when experiencing rapid postnatal weight gain. Data on the dynamic features of body weight and fat mass (FM) gain that occurs early in life is scarce. We investigated the postnatal weight and FM gain during the first five months after term in a cohort of preterm infants. METHODOLOGY/PRINCIPAL FINDINGS: Changes in growth parameters and FM were prospectively monitored in 195 infants with birth weight ≤1500 g. The infants were categorized as born adequate for gestational age (AGA) without growth retardation at term (GR−), born AGA with growth retardation at term (GR+), born SGA. Weight and FM were assessed by an air displacement plethysmography system. At five months, weight z-score was comparable between the AGA (GR+) and the AGA (GR−), whereas the SGA showed a significantly lower weight.The mean weight (g) differences (95% CI) between SGA and AGA (GR−) and between SGA and AGA (GR+) infants at 5 months were −613 (−1215; −12) and −573 (−1227; −79), respectively. At term, the AGA (GR+) and the SGA groups showed a significantly lower FM than the AGA (GR−) group. In the first three months, change in FM was comparable between the AGA (GR+) and the SGA groups and significantly higher than that of the AGA (GR−) group.The mean difference (95% CI) in FM change between SGA and AGA (GR−) and between AGA (GR+) and AGA (GR−) from term to 3 months were 38.6 (12; 65); and 37.7 (10; 65). At three months, the FM was similar in all groups. CONCLUSIONS: Our data suggests that fetal growth pattern influences the potential to rapidly correct anthropometry whereas the restoration of fat stores takes place irrespective of birth weight. The metabolic consequences of these findings need to be elucidated.